Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
[ "stage:draft", "article:topic", "authorname:thangarajahp", "calcplot:yes", "license:ccbyncsa", "showtoc:yes", "transcluded:yes" ]
Mathematics LibreTexts

4E Exercises

  • Page ID
    10317
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)

    \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)

    Exercise \(\PageIndex{1}\)

    \(\displaystyle\int_{-1}^{4} \frac{x}{\sqrt{x+4}} \, dx\)

    Answer

    Let \(u= x+4\), then \(du=dx\) and \(x=u-4\).

    Now \(\displaystyle\int_{-1}^{4} \frac{x}{\sqrt{x+4}} \, dx = \displaystyle \int_{-1}^{4} \frac{u-4}{\sqrt{u}} du\)

    \(= \displaystyle \int_{-1}^{4} {(u-4)}u^{\frac{-1}{2}} du\)

    \(=\displaystyle \int_{-1}^{4} u^{\frac{1}{2}} -4u^{\frac{-1}{2} }du\)

    \(=\left(\displaystyle\frac{2}{3} u^{\frac{3}{2}} -4 \frac{2}{1}u^{\frac{1}{2}} \right) \left |_{x=-1}^{x=4} \right.\)

    \(= \left(\displaystyle\frac{2}{3} (x+4)^{\frac{3}{2}} -8 (x+4)^{\frac{1}{2}} \right) \left |_{x=-1}^{x=4} \right.\)

    \(=\frac{2}{3} ( 8^{\frac{3}{2} }- 3 ^{\frac{3}{2}} )-8( 8^{\frac{1}{2}}- 3^{\frac{1}{2}} )\)

    \(=6\sqrt{3}-\frac{16}{3}\sqrt{2}.\)

    Exercise \(\PageIndex{2}\)

    \(\displaystyle\int_{0}^{1} x^3\sqrt{x^2+3}\, dx\)

    Answer

    Let \(u= x^2+3\), then \(du=2xdx\) and \(x^2=u-3\). Now,

    \(\displaystyle\int_{0}^{1} x^3\sqrt{x^2+3} \, dx = \displaystyle \frac{1}{2}\int_{0}^{1} x^2\sqrt{x^2+3}\, \,2xdx\)

    \(= \displaystyle \frac{1}{2}\int_{0}^{1} (u-3) \sqrt{u}\, du)\)

    \(= \displaystyle \frac{1}{2}\int_{0}^{1} (u^{\frac{3}{2}}-3 u^{\frac{-1}{2} }) \, du)\)

    \(= \displaystyle \frac{1}{2} ( \frac{2}{5} u^{\frac{5}{2}}-3 \frac{2}{1} u^{\frac{1}{2} }) \left |_{x=0}^{x=1} \right.)\)

    \(= \displaystyle \frac{1}{2} ( \frac{2}{5} (x^2+3)^{\frac{5}{2}}-3 \frac{2}{1} (x^2+3)^{\frac{1}{2} }) \left |_{x=0}^{x=1} \right.)\)

    \(= \displaystyle \frac{1}{2} \left( \frac{2}{5} ( (1^2+3)^{\frac{5}{2}} -(0^2+3)^{\frac{5}{2}} \right)-6\left((1^2+3)^{\frac{1}{2} }-(0^2+3)^{\frac{1}{2} } \right) \)

    \(= \displaystyle \frac{6\sqrt{3}}{5} -\frac{8}{5} \).

    Exercise \(\PageIndex{3}\)

    \(\displaystyle\int_{1}^{\sqrt{2}} \frac{x}{x^4+3}\, dx\)

    Answer

    Let \(u= x^2\), then \(du=2xdx\). Now,

    \(\displaystyle\int_{1}^{\sqrt{2}} \frac{x}{x^4+3}\, dx=\displaystyle \frac{1}{2}\int_{1}^{\sqrt{2}} \frac{1}{u^2+3}\, du\)

    \( =\displaystyle \frac{1}{2 \sqrt{3}} \tan^{-1} \left( \frac{u}{\sqrt{3}} \right) \left|_{x=1}^{x=\sqrt{2}} \right.\)

    \( =\displaystyle \frac{1}{2 \sqrt{3}} \tan^{-1} \left( \frac{x^2}{\sqrt{3}} \right) \left|_{x=1}^{x=\sqrt{2}} \right.\)

    \( =\displaystyle \frac{1}{2 \sqrt{3}} \left(\tan^{-1} \left( \frac{(\sqrt{2})^2}{\sqrt{3}} \right)-\tan^{-1} \left( \frac{1^2}{\sqrt{3}}\right) \right) \)

    \( =\displaystyle \frac{1}{2 \sqrt{3}} \left(\tan^{-1} \left( \frac{2}{\sqrt{3}} \right)-\tan^{-1} \left( \frac{1}{\sqrt{3}}\right) \right) \)

    \( =\displaystyle \frac{1}{2 \sqrt{3}} \left(\tan^{-1} \left( \frac{2}{\sqrt{3}} \right)-\frac{\pi}{6} \right) \)

    \( =\displaystyle \frac{\pi-6\tan^{-1} \left( \frac{2}{\sqrt{3}} \right)}{12\sqrt{3}}\).

    Exercise \(\PageIndex{4}\)

    \(\displaystyle\int_{1}^{\sqrt{2}} xe^{-x^{2}}\, dx\)

    Answer

    Let \(u= -x^2\), then \(du=-2xdx\). Now,

    \(\displaystyle\int_{1}^{\sqrt{2}} xe^{-x^{2}}\, dx= \displaystyle \frac{-1}{2}\int_{1}^{\sqrt{2} } e^u du\)

    \( = \displaystyle \frac{-1}{2}e^u \left|_{x=1}^{x=\sqrt{2}} \right.\)

    \( = \displaystyle \frac{-1}{2} e^{-x^{2}} \left|_{x=1}^{x=\sqrt{2}} \right.\)

    \( = \displaystyle \frac{-1}{2} \left( e^{-(\sqrt{2})^{2}} - e^{-1}\right) \)

    \( = \displaystyle \frac{-1}{2} \left( e^{-2} - e^{-1}\right) \)

    \( = \displaystyle \frac{e-1}{2e^2}\).

    Exercise \(\PageIndex{5}\)

    \(\displaystyle\int \frac{\sin(3x)}{e^{1+\cos(3x)} }\, dx\).

    Answer

    Let \(u=e^{-(1+\cos(3x))}\), then \(du= 3e^{-(1+\cos(3x))} \sin(3x) dx\). Now,

    \(\displaystyle\int \frac{\sin(3x)}{e^{1+\cos(3x)} }\, dx= \frac{1}{3} \int du= \frac{u}{3}+C = \frac{e^{-(1+\cos(3x))}}{6} +C.\)